Selected Papers from MEDPOWER 2018-the 11th Mediterranean Conference on Power Generation, Transmission, Distribution and Energy Conversion - Pandžić, Hrvoje; Kuzle, Igor; Capuder, Tomislav (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue presents extended versions of selected top papers of the Mediterranean Conference on Power Generation, Transmission, Distribution and Energy Conversion (MEDPOWER), held in Dubrovnik in 2018. The 11th Mediterranean Conference on Power Generation, Transmission, Distribution and Energy Conversion (MEDPOWER 2018) was held in Cavtat, Dubrobnik, Croatia, from 12 to 15 November 2018. The conference gathered more than 200 scientists, researchers, and experts from all around the world. A total of 147 oral presentations were held during the conference, with an additional 50 papers presented in special sessions. The top 10 papers have been selected for this Special Issue in Energies, covering a variety of topics from end-user challenges, distribution and transmission network operation and planning, to generation planning and modeling.